Exploratory Factor and Reliability Analysis for the Censorship Instrument of OTT Media Content in Malaysia - Isa, Asma Md.; Mahmud, Wan Amizah Wan; Azlan, Arina Anis; Sulaiman, Wan Idros Wan; Pitchan, Muhammad Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study to examine the validity and reliability the predicting factor of censorship and its relationship with the level of audience gratification on the use of OTT media services in the regulatory landscape in Malaysia. The preliminary data was obtained from questionnaires randomly distributed to 159 OTT media users in Kuala Lumpur who subscribed to OTT media services. A survey design was employed to investigate the factor structure of the censorship. Quantitative data were analysed using exploratory factor analysis (EFA) and Reliability Analysis Test using SPSS 23. The outcome of the analysis has successfully led to the formulation of new predictive factor as a result of the combination of items from the original variable. The original items in this variable correlate well in the constructs. The prediction factor in particular censorship are redesigned, arranged and reclassified based on a rational-empirical approach. The censorship predictive factor is arranged starting with the highest Eigen value as the independent variable to explain other variables. Content censorship is the dominant predictive factor influencing the audience gratification level.